2020
DOI: 10.31234/osf.io/qbgh7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Health behaviors and mental health before and during the COVID-19 pandemic: A longitudinal population-based survey

Abstract: Background: Health behaviors such as physical activity and a balanced diet are essential to promote and maintain health. Especially during a crisis, such as the COVID-19 pandemic, they have the potential to buffer against stress and protect mental health. Method: In a longitudinal study with four measurement points over 3 months during the COVID-19 pandemic, about 3,500 randomly selected participants representative of the German population reported their mental health (i.e., anxiety, depression, loneliness), s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 39 publications
0
18
1
Order By: Relevance
“…For example, one study found that individuals with higher health and diet literacy were more likely to increase healthy eating during the pandemic [ 60 ], while another reported that pro-healthy changes to diet were associated with older age and increased consumption of home cooking [ 58 ]. Another key element in dietary changes during the pandemic appears to be the role of snacking between meals [ 61 , 62 , 63 ]. While our survey did not assess whether snacking increased during the COVID-19 pandemic, the high proportion of participants reporting increased intake of snack foods and desserts suggests that intake outside of regular mealtimes could have increased in this sample as well.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study found that individuals with higher health and diet literacy were more likely to increase healthy eating during the pandemic [ 60 ], while another reported that pro-healthy changes to diet were associated with older age and increased consumption of home cooking [ 58 ]. Another key element in dietary changes during the pandemic appears to be the role of snacking between meals [ 61 , 62 , 63 ]. While our survey did not assess whether snacking increased during the COVID-19 pandemic, the high proportion of participants reporting increased intake of snack foods and desserts suggests that intake outside of regular mealtimes could have increased in this sample as well.…”
Section: Discussionmentioning
confidence: 99%
“…This study is the first to examine the heterogeneity in longitudinal changes in physical activity during the COVID-19 pandemic. Building on recent longitudinal studies, which reported a general decline in physical activity at the start of the pandemic, [10][11][12][13][14][15]25 our analyses identified six unique classes of growth trajectories of physical activity. Three of these classes were stable, showing little change over time, including the inactive (11.6%), the fairly active (22.2%) and the highly active (28.6%).…”
Section: Discussionmentioning
confidence: 99%
“…These differing trajectories may explain the inconsistent findings to date from longitudinal studies testing whether physical activity returned to pre-lockdown levels with the easing of restrictions in the UK. 10,11,14,15 This study further examined sociodemographic and health-related predictors of physical activity growth trajectories. When comparing the three stable classes (inactive, fairly active, and highly active; LC1-3), we found no gender, ethnic, or urban/rural differences between them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations